2009
DOI: 10.1073/pnas.0904638106
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila O -GlcNAc transferase (OGT) is encoded by the Polycomb group (PcG) gene, super sex combs ( sxc )

Abstract: O-linked N-acetylglucosamine transferase (OGT) reversibly modifies serine and threonine residues of many intracellular proteins with a single ␤-O-linked N-acetylglucosamine residue (O-GlcNAc), and has been implicated in insulin signaling, neurodegenerative disease, cellular stress response, and other important processes in mammals. OGT also glycosylates RNA polymerase II and various transcription factors, which suggests that it might be directly involved in transcriptional regulation. We report here that the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
199
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(209 citation statements)
references
References 41 publications
10
199
0
Order By: Relevance
“…3). This and other results of the present study support previous observations that OGT and EZH2/PRC2 are functionally associated with each other (34,35,37). Nevertheless, discrepancy still exists.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…3). This and other results of the present study support previous observations that OGT and EZH2/PRC2 are functionally associated with each other (34,35,37). Nevertheless, discrepancy still exists.…”
Section: Discussionsupporting
confidence: 86%
“…Sxc/Ogt, the Drosophila homolog of mammalian OGT, was identified as a polycomb group (PcG) protein involving in polycomb repression during larvae development (34,35). The chromosomal location of O-GlcNAc coincides with the PcG response elements in both Drosophila (34,35) and Caenorhabditis elegans (36).…”
mentioning
confidence: 99%
“…OGT is essential for embryonic stem cell viability and somatic cell function (O'Donnell et al 2004;Shafi et al 2000). Deletion of OGT in Arabidopsis (Jacobsen et al 1996), Drosophila (Sinclair et al 2009;Gambetta et al 2009), and mice is lethal (Shafi et al 2000), and leads to dauer phenotypes in Caenorhabditis elegans (Hanover et al 2005), suggesting that O-GlcNAc is essential for cellular homeostasis.…”
Section: O-glcnac Transferasementioning
confidence: 99%
“…Previous studies have hinted at a role for O-GlcNAc in transcriptional repression (29,41,42). Two recent papers have demonstrated that Drosophila ogt is allelic with super sex combs (sxc), a gene involved in repression of homeotic genes (13,14). Flies deficient in catalytically Fig.…”
Section: Disruption Of O-glcnac Cycling Affects the Aging Pathway Andmentioning
confidence: 99%
“…active Ogt develop through all larval stages, but die as pharate adults that have a variety of homeotic transformations (13,14,43). Polyhomeotic (Ph), a Polycomb group (PcG) protein, was shown to be OGlcNAc modified and was suggested to be the mediator of OGTdependent repression.…”
Section: Disruption Of O-glcnac Cycling Affects the Aging Pathway Andmentioning
confidence: 99%